Enhanced oral absorption of pemetrexed by ion-pairing complex formation with deoxycholic acid derivative and multiple nanoemulsion formulations: preparation, characterization, and in vivo oral bioavailability and anticancer effect - Pangeni R (Dove Medical Press, 2018)
Rudra Pangeni,1,* Jeong Uk Choi,2,* Vijay Kumar Panthi,1 Youngro Byun,3 Jin Woo Park1 1College of Pharmacy and Natural Medicine Research Institute, Mokpo National University, Muan-gun, Jeonnam, Republic of Korea; 2College of Pharmacy, Seoul National University, Seoul, Republic of Korea; 3Department of Molecular Medicine and Biopharmaceutical Science, Graduate School of Convergence Science and Technology, College of Pharmacy, Seoul National University, Seoul, Republic of Korea *These authors contributed equally to this work Objective: The current study sought to design an oral delivery system of pemetrexed (PMX), a multitargeted antifolate antimetabolite, by enhancing its intestinal membrane permeability. Materials and methods: PMX was ionically complexed with a permeation enhancer such as Nα-deoxycholyl-l-lysyl-methylester (DCK) and prepared as an amorphous solid dispersion by mixing with dispersants such as 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CD) and poloxamer 188 (P188), forming an HP-beta-CD/PMX/DCK/P188; the complex was incorporated into multiple water-in-oil-in-water nanoemulsions in a supersaturated state (HP-beta-CD/PMX/DCK/P188-NE). Results: After complex formation, the partition coefficient and in vitro membrane permeability of PMX were markedly increased, but it showed similar cytotoxic and inhibitory effects on cancer cell proliferation/migration. Furthermore, the intestinal membrane permeability and epithelial cell uptake of PMX were synergistically improved after HP-beta-CD/PMX/DCK/P188 was incorporated into a nanoemulsion with a size of 14.5±0.45 nm. The in vitro permeability of HP-beta-CD/PMX/DCK/P188-NE across a Caco-2 cell monolayer was 9.82-fold greater than that of free PMX, which might be attributable to the partitioning of PMX to the epithelial cells being facilitated via specific interaction of DCK with bile acid transporters, as well as the enhanced lipophilicity accompanied by surfactant-induced changes in the intestinal membrane structure and fluidity. Therefore, the oral bioavailability of HP-beta-CD/PMX/DCK/P188-NE in rats was evaluated as 26.8%±2.98% which was 223% higher than that of oral PMX. Moreover, oral HP-beta-CD/PMX/DCK/P188-NE significantly suppressed tumor growth in Lewis lung carcinoma cell-bearing mice, and the tumor volume was maximally inhibited by 61% compared with that in the control group. Conclusion: These results imply that HP-beta-CD/PMX/DCK/P188-NE is an effective and promising delivery system for enhancing the oral absorption of PMX. Thus, there is the potential for new medical applications, including applications in metronomic cancer treatment. Keywords: pemetrexed, deoxycholic acid derivative, multiple nanoemulsions, permeability, oral absorption, oral anticancer therapy